Active drag measurements in elite US swimmers. - Cappaert, J. M.; Kolmogorov, S.; Walker, J.; Skinner, J.; Rodriguez, F.; Gordon, B. J. (Medicine & Science in Sports & Exercise, 1996)
Male swimmers had twice as much active drag and power output as females in both strokes. Their swimming velocities were at least 0.2 m/s faster than the females. The more objective parameter of the hydrodynamic coefficient seemed to slightly favor the overall swimming technique of females.